Analysis of seaports development strategies: science, technology, education and marketing - Ilnytskyy, Denys; Zinchenko, Sergii; Savych, Oleksandr; Yanchetskyy, Oleksandr (Technology audit and production reserves, 2018)
The paper investigates the development of domestic and foreign seaports in conditions of growth of global competition, implementation of aggressive policies and strategies by competitors. The most problematic aspects in improving the performance of modern functions by seaports (integration, service, image) are: ignorance of interests of key stakeholders, insufficient use of all development factors, lack of understanding of global trends and competitive conditions for infrastructure development and its interconnections with land infrastructure; which are incorporated in strategies. The research study of scientific and analytical works and strategies for seaports’ development at the level of industry and enterprises, used methodology for constructing competitive map of global port market, systematization of factors and generalization of modern techniques for studying trends and features of seaports’ development, and micro- and macroeconomic indicators of their activities. As a result, the list of stakeholders of seaports’ development was defined, a matrix of developmental factors was offered and competitive maps of world port market with positions of countries and ports were constructed. The analysis of competitive maps revealed significant asymmetries in dynamics and size of market segments of seaports and countries, which results from implementation of unique national, regional and local strategies. The key factor of their development is the active use of public-private partnerships, scientific and educational, technological and marketing factors. Global trends (containerization, ecologization and decentralization) are revealed and recommendations on key development indicators are proposed: revision of the role of the state; consideration of interests of stakeholders; deregulation; joining of systematic and individual approaches to each port; improving the quality of monitoring and developing interrelations with the scientific and educational systems; application of marketing tools. Their implementation in developmental strategies will improve efficiency of use of seaports in Ukraine and related industries.